Multiplatform Visual Novel for Culture Education in a Part of Using ICT for Developing a Lifelong Learning - Moechammad Sarosa; Zamah Sari; Suhari Suhari; Hilmy Bahy Hakim (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Over the past decade, ICT (Information Communication Technology) have enabled changes in the way people live, work, interact and acquire knowledge. In Indonesia, the progress of using ICT for education and training has growing rapidly, it called E-learning. However, until this time, they still have limitations in a term of system, platform, and usage. E-learning system that we are using until now, one of these, they are usually only available in web-based system take a small part of supporting the whole basic education such as Science and IT only. Teaching social and culture is very important especially when the students still at elementary school. There is a good point for developing software that could teach these students about Indonesia’s social and culture that can be accessed whenever and wherever they are available. Therefore we create the application in a form of visual novel that can be used in multiple platforms. Here, we will present the Visual Novel that used for moral education, there will be a story about honesty, be grateful, helping each other etc.